Comparison of the Electrochemical Behavior of Iodide Ion in Hydrophobic/Hydrophilic Ionic Liquids. Issue 2 (1st February 2022) - Lebedeva, Olga; Kuznetsova, Irina; Kultin, Dmitry; Kustov, Leonid
Abstract : The electro-oxidation of iodide has been investigated using cyclic voltammetry on a platinum electrode in ionic liquids tributylmethylammonium bis(trifluoromethylsulfonyl)imide (N4441 NTf2 ), trioctylmethylammonium salicylate (TOMAS) and 1-butyl-3-methylimidazolium tetrafluoroborate (BmimBF4 ). The hydrophobic/hydrophilic TOMAS ionic liquid was used for the first time in electrochemical research. Two electro-oxidation processes are observed in all of the investigated ionic liquids. The calculation of the number of electrons corresponding to every electro-oxidation stage suggested that in N4441 NTf2 electro-oxidation follows a different path than those described in the literature. The hydrophobicity/hydrophilicity of ionic liquids affects electrochemical processes. It was shown that the best electrolyte for electro-oxidation of iodide is hydrophobic ionic liquid N4441 NTf2 .